2010
DOI: 10.1210/jc.2009-1611
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Deficiency after Treatment of Acromegaly: A Randomized, Placebo-Controlled Study of Growth Hormone Replacement

Abstract: This is the first randomized, placebo-controlled study of the effects of GH replacement therapy on body composition and cardiovascular end points in patients who have developed GH deficiency after treatment for acromegaly, a disease complicated by metabolic and body composition alterations and increased cardiovascular risk. GH replacement decreased visceral adipose tissue, increased fat-free mass, decreased hsCRP, and improved quality of life in patients with GHD after cure of acromegaly, with minimal side eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 50 publications
3
34
0
1
Order By: Relevance
“…However, whether the increased rate of vascular events was due to the impaired metabolic profile or other patient characteristics at baseline or due to GH treatment itself could not be addressed properly due to the small study population and relatively short follow-up in that study. Thereafter, this safety concern is restated by others, but could not be verified or retested (17,18). Recently, Tritos et al (28) have found a comparable safety profile in patients with previous acromegaly and NFPA, with the exception of an elevated cardiovascular mortality rate.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 4 more Smart Citations
“…However, whether the increased rate of vascular events was due to the impaired metabolic profile or other patient characteristics at baseline or due to GH treatment itself could not be addressed properly due to the small study population and relatively short follow-up in that study. Thereafter, this safety concern is restated by others, but could not be verified or retested (17,18). Recently, Tritos et al (28) have found a comparable safety profile in patients with previous acromegaly and NFPA, with the exception of an elevated cardiovascular mortality rate.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…To date, ten studies (Table 4) investigated the characteristics of GHD and/or the effect of GH treatment on cardiovascular outcome measures in GHD patients after treatment for acromegaly (6,15,16,17,18,19,20,26,27,28). In three studies, patients who were GH sufficient after treatment for acromegaly or active acromegaly were used as controls.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 3 more Smart Citations